Bilateral Diffuse Tumorous Pseudoangiomatous Stromal Hyperplasia: A Case of Bilateral Mastectomy in a 29-Year-Old Woman - Hongyan Dai; Carol Connor; Wei Cui; Jason Gatewood; Fang Fan (Case Reports in Pathology)
Pseudoangiomatous stromal hyperplasia (PASH) is a benign breast lesion commonly encountered as an incidental microscopic finding. However, it can also manifest as a mass-forming lesion (tumorous PASH) capable of recurrence after surgical excision. Most of the previously reported cases of tumorous PASH present as a single dominant mass. Here we reported a rare case of diffuse tumorous PASH involving bilateral breasts clinically mimicking malignancy. A 29-year-old African-American female presented with a one-year history of bilateral breast enlargement and asymmetry. Physical examination revealed multiple palpable nodules in bilateral breasts. Imaging studies demonstrated innumerable homogeneously enhancing masses throughout both breasts, greater on the left, with multiple cysts and edema. Biopsy of the breast nodules demonstrated histopathological changes consistent with PASH. Due to the extent of the lesions and progressive clinical symptoms, decision was made to perform bilateral mastectomy. Macroscopic examination of the bilateral mastectomy specimens revealed markedly enlarged breasts with marked edema and numerous well-defined firm nodules. Microscopic evaluation of the nodules confirmed the diagnosis of PASH. No evidence of malignancy was identified. Recognition of this rare form of PASH is essential for the proper clinical management.